About existence of resilient supervisors against smart sensor attacks - Su, Rong (2023)
One key challenge of cybersecurity of discrete event systems (DES) is how to ensure system resilience against sensor and/or actuator attacks, which may tamper data integrity and service availability. In this paper we discuss decidability issues related to smart sensor attacks. We first present a sufficient and necessary condition that ensures the existence of a smart sensor attack, which reveals a novel demand-supply relationship between an attacker and a controlled plant, represented as a set of risky pairs. Each risky pair consists of a damage string desired by the attacker and an observable sequence feasible in the supervisor such that the latter induces a sequence of control patterns, which allows the damage string to happen. It turns out that each risky pair can induce a smart weak sensor attack. Next, we show that, when the plant, supervisor and damage language are regular, it is possible to remove all such risky pairs from the plant behaviour, via a genuine encoding scheme, upon which we establish our key result that the existence of a nonblocking supervisor resilient against all smart sensor attacks is decidable.